Anemia, hematinic deficiencies, hyperhomocysteinemia, and gastric parietal cell antibody positivity in burning mouth syndrome patients with or without microcytosis - Ying-Tai Jin; Yang-Che Wu; Yu-Hsueh Wu; Julia Yu-Fong Chang; Chun-Pin Chiang; Andy Sun (Elsevier, 2021)
Background/purpose: Microcytosis is defined as having mean corpuscular volume <80 fL. This study evaluated whether 68 burning mouth syndrome (BMS) patients with microcytosis and 816 BMS patients without microcytosis had higher frequencies of anemia, hematinic deficiencies, hyperhomocysteinemia, and serum gastric parietal cell antibody (GPCA) positivity than 442 healthy control subjects. Materials and methods: Complete blood count and serum iron, vitamin B12, folic acid, homocysteine, and GPCA levels in 68 BMS patients with microcytosis, 816 BMS patients without microcytosis, and 442 healthy control subjects were measured and compared. Results: We found that 73.5%, 44.1%, 4.4%, 2.9%, 13.2%, and 10.3% of 68 BMS patients with microcytosis and 15.3%, 13.8%, 4.8%, 2.2%, 19.7%, and 12.5% of 816 BMS patients without microcytosis had blood hemoglobin, iron, vitamin B12, and folic acid deficiencies, hyperhomocysteinemia, and serum GPCA positivity, respectively. Both 68 BMS patients with microcytosis and 816 BMS patients without microcytosis had significantly higher frequencies of blood hemoglobin, iron, vitamin B12, and folic acid deficiencies, hyperhomocysteinemia, and serum GPCA positivity than 442 healthy control subjects (all P-values < 0.05). Moreover, 68 BMS patients with microcytosis had significantly higher frequencies of blood hemoglobin and iron deficiencies than 816 BMS patients without microcytosis. Conclusion: There are significantly higher frequencies of anemia, serum iron, vitamin B12, and folic acid deficiencies, hyperhomocysteinemia, and serum GPCA positivity in BMS patients with or without microcytosis than in healthy control subjects. BMS patients with microcytosis have significantly higher frequencies of blood hemoglobin and iron deficiencies than BMS patients without microcytosis.